Pengembangan Jalur Pejalan Kaki Kawasan Central Business District (CBD) Kota Makassar - Imam Nur Alam; Ananto Yudono; Ihsan Ihsan (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The development of cities in Indonesia brought many changes to the internal conditions of the city, where population growth and rapid regional development were built mainly in the downtown area, giving rise to the high need for urban facilities and utilities such as pedestrian paths. Therefore planning is carried out to create a pedestrian path that meets the principles of interactive, comfortable and safe. The objectives of this plan are (1) to know the trend of the gap between existing conditions in the planning area and the principles of the pedestrian path that are viewed from the interaction between pedestrians, (2) to find out what factors have a significant effect on the gap between existing with ideal conditions, (3) preparing a pedestrian path plan that meets the principles of interactive, comfortable, and safe for pedestrians. The analysis technique used is site analysis is the analysis used in a non-physical city design and is also used to formulate space programs based on user activity characteristics and space activities. The other understanding of site analysis is the analysis used in a non-physical city design and used also to formulate space programs based on the characteristics of user activities and space activities. Data collection is done by field observation. The results of the planning in the form of a pedestrian path that meets attractive principles of the form of a simple pedestrian path but are made as elegant as possible, comfortable to avoid various obstacles and safe for pedestrians.